Lymphoedema, a significant health problem in Israel: A descriptive community‐based study. Issue 5 (25th November 2020) - Tidhar, Dorit; Deutscher, Daniel; Armer, Jane M.
Abstract: Lymphoedema (LE) is recognised as a chronic disabling disease. Knowledge on patient characteristics, treatments, and outcomes in Israel is lacking. The aim of the study was to (a) describe demographic and health characteristics, treatments, utilisation, and functional outcomes of patients receiving physical therapy due to LE in a large nationwide healthcare provider in Israel; and (b) assess the feasibility of conducting a future practice‐based evidence (PBE) study. This is a retrospective observational cohort study. Descriptive analyses of an electronic medical record database were performed. Data from 6013 patient episodes were analysed. A high proportion of patients had two or more comorbidities (80%) and chronic medication use (85%) with increasing rates over the 8‐year period. The most frequent LE classification was stage 2 (45%). A majority of LE was in the lower limbs (51%) with increasing rates over the years. The most frequent treatment‐related activity was measuring limb circumference and the most frequent intervention was educating for self‐management. This study provides a first comprehensive description of patient characteristics receiving physical therapy for LE in Israel. The available database offers an opportunity for PBE studies. Recommendations for improvements in specific data collection processes were identified.